Simple feedback of colonoscopy performance improved the number of adenomas per colonoscopy and serrated polyp detection rate - Toyoshima, Osamu; Yoshida, Shuntaro; Nishizawa, Toshihiro; Yamakawa, Tadahiro; Arano, Toru; Isomura, Yoshihiro; Kanazawa, Takamitsu; Ando, Hidehiko; Tsuji, Yosuke; Koike, Kazuhiko (Endoscopy International Open, 2021)
Background and study aims High-quality endoscopy requires improvement of not only the adenoma detection rate (ADR) but also the serrated polyp (SP) detection rate and the mean number of adenomas per positive procedure (MAP +). We evaluated whether a simple feedback of colonoscopy performance improves those quality indicators using propensity-score matching.Patients and methods Eleven endoscopists were evaluated regarding colonoscopy performance including ADRs, SP detection rates, mean numbers of adenomas per procedure (MAPs), and MAPs + with their ranking in the clinic. Endoscopic performance was compared before and after the feedback.Results Colonoscopies were performed for 874 patients before the feedback and 1,272 patients after the feedback. Using propensity-score matching, 803 patients before the feedback and 803 patients after the feedback were matched. ADR after the feedback was significantly higher than that before the feedback (50.8 % and 40.8 %, respectively). MAP after feedback was significantly larger than that before the feedback (0.92 and 0.69, respectively), as well as MAP + (1.96 and 1.69, respectively). Clinically significant SP detection rate was also improved from 10.0 % to 14.9 %.Conclusions Feedback including ADR, MAP, MAP +, and clinically significant SR detection rate could improve on those quality indicators. Further studies are needed to effectively prevent colorectal cancer in colonoscopy practice.